IMPLEMENTASI KEYAKINAN KELAS PADA SEKOLAH DASAR BERBASIS SEKOLAH RAMAH ANAK - Ragil Aria Irawan; Muhardila Fauziah (STKIP Subang, 2024)
Uncomfortable, safe, and conducive classrooms are one of the causes of less optimal learning and a less supportive environment for school activities. To overcome this can be applied class beliefs. This is in line with the implementation of child-friendly schools. This study was designed to analyze the application of classroom beliefs to child-friendly schools. Research uses descriptive qualitative research methods. The data sources used are from observations, interviews, and documentation. The result of this study was the implementation of an already good child-friendly school with the support of various parties, facilities, and policies implemented. For confidence, the classroom is a child-friendly school program at Sonosewu Elementary School which is still in its infancy so there are still some factors that are present such as poor student environment, parental participation, and family environment conditions. For its supporting factors are school facilities, student participation, school citizens, and commitment.